Metallurgy, Ballistics and Epistemic Instruments: The Nova scientia of Nicolò Tartaglia – A New Edition - Matteo Valleriani,Valleriani,Matteo (Edition Open Access, 2013)
In 1537, Nicolò Tartaglia (1500–1557), a mathematician from Brescia, published
Keywords: Renaissance; violent motion; quadrant; MPRL; Edition Open Access; metallurgy; Tartaglia; mechanics; ballistics; artillery